2015
DOI: 10.3109/07434618.2014.995779
|View full text |Cite
|
Sign up to set email alerts
|

Using Dynamic Assessment to Evaluate the Expressive Syntax of Children who use Augmentative and Alternative Communication

Abstract: The developmental readiness of four 5-year-old children to produce basic sentences using graphic symbols on an augmentative and alternative communication (AAC) device during a dynamic assessment (DA) task was examined. Additionally, the ability of the DA task to predict performance on a subsequent experimental task was evaluated. A graduated prompting framework was used during DA. Measures included amount of support required to produce the targets, modifiability (change in participant performance) within a DA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 39 publications
3
28
0
2
Order By: Relevance
“…The first focused on phonological awareness skills (Barker, Bridges, & Saunders, 2014), and the second, a precursor to the current investigation, used graduated prompting to evaluate productions of early two-and threeword utterances with four 5-year-old children with severe speech impairments (King, Binger, & Kent-Walsh, 2015). Results from the latter study indicated that the participants benefited from a range of cues to produce the sentences.…”
Section: Da For Children Who Require Aacmentioning
confidence: 85%
“…The first focused on phonological awareness skills (Barker, Bridges, & Saunders, 2014), and the second, a precursor to the current investigation, used graduated prompting to evaluate productions of early two-and threeword utterances with four 5-year-old children with severe speech impairments (King, Binger, & Kent-Walsh, 2015). Results from the latter study indicated that the participants benefited from a range of cues to produce the sentences.…”
Section: Da For Children Who Require Aacmentioning
confidence: 85%
“…First, many children with severe speech impairmentsincluding those eventually diagnosed with either speech sound or motor speech disorders-may require intervention not only for speech but also for language (e.g., McNeill & Gillon, 2013;Mortimer & Rvachew, 2010), but language may be overlooked in favor of focusing on the most obvious issue. In addition, and somewhat to the converse, language expectations may be set too low for many of these children -that is, clinicians may underestimate the language potential for a child whose speech is unintelligible, in particular for children with motor speech disorders; that is, the speech impairment may mask linguistic competence, a phenomenon illustrated by studies showing that preschoolers with severe speech impairments can rapidly learn to create multisymbol messages using graphic symbols even though the ability to do so may not be reflected clearly in their spoken language Binger, KentWalsh, Ewing, & Taylor, 2010;Binger, Kent-Walsh, King, Webb, & Buenviaje, in press;Kent-Walsh, Binger, & Buchanan, 2015;King et al, 2015).…”
Section: Language Assessment and Speech Impairmentsmentioning
confidence: 99%
“…A quite different but complementary approach that may be used to examine syntax for children with limited word productions is to explore expressive syntax by using aided AAC. For example, nearly all children in the current investigation (including Child N) learned to produce two-to three-symbol rule-based messages (e.g., agent-action-object sentences) during a relatively brief dynamic assessment task in which children used a communication app on an iPad (Binger, Kent-Walsh, & King, in press;King et al, 2015). Thus, alternative communication modes should be considered when assessing expressive language potential for children with severe speech Figure 2.…”
Section: Viability Of the Language Samplesmentioning
confidence: 99%
See 2 more Smart Citations